2019
DOI: 10.1093/rb/rbz026
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the physicochemical properties of nano-hydroxyapatite/collagen and natural bone ceramic/collagen scaffolds and their osteogenesis-promoting effect on MC3T3-E1 cells

Abstract: The use of various types of calcium phosphate has been reported in the preparation of repairing materials for bone defects. However, the physicochemical and biological properties among them might be vastly different. In this study, we prepared two types of calcium phosphates, nano-hydroxyapatite (nHA) and natural bone ceramic (NBC), into 3D scaffolds by mixing with type I collagen (CoL), resulting in the nHA/CoL and NBC/CoL scaffolds. We then evaluated and compared the physicochemical and biological properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 59 publications
(69 reference statements)
2
24
0
Order By: Relevance
“…In addition, the nano-sized particles have an affinity and can induce deposition on irregular spaces (22) . This was also confirmed by researches as Lei X et al (23) who reported that Nano-hydroxyapatite is the most similar compound to the dental tissue having characteristics such as biological compatibility, remineralization potential, antimicrobial growth and nanoparticles size.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, the nano-sized particles have an affinity and can induce deposition on irregular spaces (22) . This was also confirmed by researches as Lei X et al (23) who reported that Nano-hydroxyapatite is the most similar compound to the dental tissue having characteristics such as biological compatibility, remineralization potential, antimicrobial growth and nanoparticles size.…”
Section: Discussionsupporting
confidence: 65%
“…Previous studies have shown that heparinized β-tricalcium phosphate (β-TCP) supports the adhesion and proliferation of rat MSC and is expected to differentiate into osteoblast lineage compared with β-TCP and control [21] . In another study, natural bone ceramics/type I collagen could promote the expression of early osteogenic genes, while nano-hydroxyapatite (nHA)/COl could up-regulate the expression of late osteogenic genes [22] . Liu Through cell-level research, LGR6 is highly expressed in osteoblast progenitor cells and enhances the Wnt signalling pathway by enhancing the stability of β-Catenin to promote osteogenesis [23] .…”
Section: Discussionmentioning
confidence: 99%
“…This is a natural piezoelectric material with a piezoelectric coefficient in the range from 0.2 to 2.0 pC/N [260]. Research has been reported on the application of collagen scaffolds in bone healing [261][262][263][264]. Furthermore, collagen-calcium phosphate composites have been reported for cartilage tissue engineering [265].…”
Section: Collagenmentioning
confidence: 99%